L’interférence comme particularité du « français cassé » en Algérie - Medane, Hadjira (Travaux interdisciplinaires du Laboratorie parole et langage d'Aix-en-Provence, 2015)
In Algeria, linguistic diversity has been the subject of several studies. The resulting sociolinguistic facts identify the degree of contact and mixing of languages in Algeria. The languages presented in this area, and which coexist with each other, do not share the same importance or the same prestige. The coexistence of two or more languages implies that they are used in different contexts, regions and even interlocutors, by members of the company to fulfill various functions. The Algerian speaker uses all the available language resources in his linguistic landscape, which has fostered the creativity of the subject speaking Algerian in French. The language practices of French by Algerian speakers are constantly changing. This innovation “is distinguished in its form and content in a clear difference from the exogenous norm of the standard French.” (Derradji, 1999:71). Based on the observation of the complexity related to the coexistence of languages in Algeria, the symbolic values that these languages convey and the particular use of French in Algeria, we are interested in what Algerians call the “broken French”. It is a phenomenon resulting from contacts between the French and the languages or language varieties, including their performances, which are presented in the Algerian linguistic landscape. This is an incorrect implementation of the French language related, it seems, to all the images and representations of the language. Therefore, it is about a particular use of French by Algerian speakers. This linguistic practice forms the peculiarity of the spoken French in Algeria. It is about the use of the French language in which many phenomena are present: interference, calque, neologisms, borrowing...etc. During this work, we wanted to investigate in an area that connects the linguistic fact to sociolinguistics. This is a study of the manifestations of the “broken French” used in Algeria. This usage results from contact between the French and Arabic (with its varieties). This is an incorrect implementation of the French language related, it seem, to all the images and representations of the language and dynamics of linguistic systems that are present in various contexts. This usage is also a feature of spoken French in Algeria. Our contribution is a part of an investigation of the peculiarities of the “broken French” used in Algeria. Our work is the description and analysis of the manifestations of this phenomenon. We offer a qualitative approach through the analysis of 20 young Algerians productions. Based on the principle of contrastive analysis, we will see how the interference is one of the peculiarities of this use. This study attempts also to see if the linguistic interferences constituting the use of French called “broken” are related to extra-linguistic factors and / or specific representations. Our research was conducted in two Algerian cities: Chlef and Tlemcen. We asked 20 young people to comment on a number of images that deal with topics related to Algerian youth using what they call the “broken French”, using recording process. Depending on this technique of investigation, we aim an analysis of language data while observing the peculiarities of the phenomenon of “broken French”. After listening to the recordings of the young respondents, we sought the mistakes made by young people. In order to group them into different types, we performed several plays. First, we tried to identify then we classified them for interpretation. The constitution and the observation of the corpus were possible because of the transcription of recorded productions.After the analysis of errors committed by youth during the recordings, it appears that the incorrect use of French in what they call the “broken French” is due to the phenomenon of interference. In this paper, we do not report all kinds of errors but only those involving the interference of the two languages: Arabic and French. The errors revealed by the corpus allowed us to distinguish three types of interference: phonetic, lexical-semantic and syntactic. Data analysis has shown that interference is the basis of what the Algerian young people call the “broken French”. While using the French, Algerian speaker refers to the structure and function (phonetic, lexical, syntactic and semantic) of his language, that its structures are incompatible with that of the French. Thus, the socio-cultural factors are certainly indicative in the production of interference but do not forget the role of representational implication of the speaker, which could also cause interference during the use of French making our case: “broken”.